As trajetórias desenvolvimentistas de Brasil e Coreia do Sul na semiperiferia: um estudo histórico comparativo a partir de suas inserções na divisão internacional do trabalho - Espindola, Guilherme Boscardin (2021)
Brazil and South Korea, two developmental states that became industrial exponents in their respective regional spheres, followed paths that incurred in different insertions of their economies in the international division of labor. The industrialization process of the peripheral countries that contextualized the cases made the term "semiperiphery" emerge among the classical dual notion between center and periphery in academia. However, the South Korean economy has diverged intensely from the Brazilian trajectory, where the "Asian tiger" is seen today in broad consensus as a protagonist actor within the technological scenario of the international division of labor, in contrast to the evident decomplexification and reprimarization of the Brazilian commercial insertion. Given the extensive scientific production that already exists that addresses the cases under different premises and theories, this paper intends to analyze the cases within an eclectic theoretical scope that addresses the singularity of the cases within a totalizing vision framed by the world-system. Therefore, the work aims at understanding the trajectory of Brazil and South Korea in the pro-systemic (capitalist) semi-periphery from the way their developmental projects were related to the North American systemic cycle of accumulation, using an approach that departs from the dialogue of the world-system with the notion of techno-economic paradigm, aiming at the more accurate framing of the notion of central activity within the international division of labor. Thus, this paper discusses the divergent unfolding of these trajectories, starting from the following research problem: how did the different approaches of Brazil's and South Korea's developmental strategies towards the North-American systemic cycle of accumulation reflect in their trajectories in the international division of labor? To answer this question, this work used a comparative process tracing of the insertion of the countries in the international division of labor, mirroring the two moments of the North American systemic cycle of accumulation, starting from the analysis of the capacity of internalization of the central activities of the metal-chemical to the microelectronic paradigm. The study concluded that the internationalist strategy, outlined by Brazil, stabilized it in the semiperiphery and the nationalist strategy of South Korea placed it at the center of the international division of labor, in which each one fulfilled a specific role of the same process within the North American systemic cycle of accumulation.